Differential Diagnosis of Vitritis in Adult Patients. (19th May 2021) - Touhami, Sarah; Leclercq, Mathilde; Stanescu-Segall, Dinu; Touitou, Valérie; Bodaghi, Bahram
ABSTRACT: The term "vitritis" refers to the presence of a cellular infiltration of the vitreous body, usually in the context of an intraocular inflammation, but not exclusively. Intermediate uveitis is the most prominent cause of vitritis, including infectious and auto-immune/auto-inflammatory etiologies. Corticosteroids and immunosuppressive therapies should not be started before ruling out the infectious causes of vitritis, especially in immunosuppressed individuals. Other situations can mimic intermediate uveitis such as amyloidosis and ocular tumors. Primary intraocular lymphoma should always be suspected in case of vitreous infiltrations in individuals aged over 50 years.